Adhesion G‐protein coupled receptors and extracellular matrix proteins: Roles in myelination and glial cell development. Issue 4 (11th January 2017) - Mehta, Paulomi; Piao, Xianhua
Abstract : Adhesion G protein‐coupled receptors (aGPCRs) are a large family of transmembrane proteins that play important roles in many processes during development, primarily through cell–cell and cell–extracellular matrix (ECM) interactions. In the nervous system, they have been linked to the complex process of myelination, both in the central and peripheral nervous system. GPR126 is essential in Schwann cell‐mediated myelination in the peripheral nervous system (PNS), while GPR56 is involved in oligodendrocyte development central nervous system (CNS) myelination. VLGR1 is another aGPCR that is associated with the expression of myelin‐associated glycoprotein (MAG) which has inhibitory effects on the process of nerve repair. The ECM is composed of a vast array of structural proteins, three of which interact specifically with aGPCRs: collagen III/GPR56, collagen IV/GPR126, and laminin‐211/GPR126. As druggable targets, aGPCRs are valuable in their ability to unlock treatment for a wide variety of currently debilitating myelin disorders. Developmental Dynamics 246:275–284, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: GPR126 regulates Schwann cells. GPR56 regulates oligodendrocytes. Extracellular matrix proteins have important roles in regulating both PNS and CNS myelination.